Internet connectivity disruption in MK (North Macedonia) - Voidly (2026)
CRITICAL severity disruption detected in North Macedonia. Confidence: 67%. Data sourced from IODA.
Network Disruption Incident ID: MK-2026-0009
Keywords: internet disruption; MK; disruption; critical